Comparison of Clinical Laboratory Assays for Measuring Serum Infliximab and Antibodies to Infliximab. (15th October 2019) - Willrich, Maria Alice V; Lazar-Molnar, Eszter; Snyder, Melissa R; Delgado, Julio C
Abstract: Background: Infliximab (IFX) is a chimeric monoclonal antibody targeting tumor necrosis factor-α, used for the management of autoimmune and inflammatory diseases. Immunogenicity to this protein drug may lead to therapeutic failure. Laboratory testing for serum IFX and antidrug antibodies (ADAs) is available for the evaluation of clinical nonresponsiveness. The purpose of this study was to compare the performance of testing methodologies used by 2 clinical reference laboratories for the quantification of IFX and detection of ADAs. Methods: Deidentified serum samples submitted for clinical testing were selected (n = 120) and tested at both sites. A trypsin-based LC-MS/MS assay for IFX and a bridging electrochemiluminescent immunoassay (ECLIA) for ADAs (Mayo Clinic) and a functional cell-based reporter gene assay (RGA) to measure both bioactive drug concentrations and neutralizing ADAs (ARUP Laboratories) were compared. Results: In all, 105 samples had measurable concentrations of IFX by both methods and yielded a correlation coefficient ( r ) = 0.917, slope = 1.028, and intercept = −0.377. One outlier measured <1.0 μg/mL by LC-MS/MS and 37 μg/mL by RGA, which was confirmed to be attributed to the presence of adalimumab. Regarding detection of ADAs, 81 of 120 samples were negative by ECLIA and RGA, whereas 30 of 120 were positive by both methods, resulting in an overall 92.5% agreement. Conclusion: Although there are substantial methodological differences in the assays used for detecting IFX and ADAs, results show significant concordance between the clinically validated methodologies performed in different laboratories.